Biocontrol Potentials of Antimicrobial Peptide Producing Bacillus Species: Multifaceted Antagonists for the Management of Stem Rot of Carnation Caused by Sclerotinia sclerotiorum - Vinodkumar, S.; Nakkeeran, S.; Renukadevi, P.; Malathi, V. G. (Frontiers in Microbiology, 2017)
Bacillus species are widely exploited as biocontrol agents because of their efficiency in impeding various plant pathogens with multifaceted approach. In this study, Bacillus species were isolated from rhizosphere of various plants viz., carnations, cotton, turmeric, and bananas in Tamil Nadu state of India. Their potential to control the growth of Sclerotinia sclerotiorum was assessed in vitro by dual plate and partition plate techniques. B. amyloliquefaciens strain VB7 was much effective in inhibiting mycelial growth (45% inhibition of over control) and sclerotial production (100%). PCR detection of AMP genes revealed that B. amyloliquefaciens (VB7) had a maximum of 10 diverse antibiotic biosynthesis genes, namely, ituD, ipa14, bacA, bacD, bamC, sfP, spaC, spaS, alba, and albF, that resulted in production of the antibiotics iturin, bacilysin, bacillomycin, surfactin, subtilin and subtilosin. Further, metabolites from B. amyloliquefaciens strains VB2 and VB7, associated with inhibition of S. sclerotiorum, were identified as phenols and fatty acids by gas chromatography mass spectrometry (GC-MS). Delivery of liquid formulations of the effective strains of Bacillus spp. as root dip was found promising for the management of stem rot of cultivated carnations. Minimal percent disease incidence (4.6%) and maximum plant growth promotion was observed in the plants treated with B. amyloliquefaciens (VB7).